Le pouvoir des mots : politique du performatif - Butler, Judith (Éditions Amsterdam, 2004)
Dans Le Pouvoir des mots, Judith Butler analyse les récents débats, souvent passionnés, sur la pornographie, la violence verbale dirigée contre les minorités et l'interdiction faite aux homosexuels membres de l'armée américaine de se déclarer tels. Il s'agit pour elle de montrer le danger qu'il y a à confier à l'État le soin de définir le champ du dicible et de l'indicible. Dans un dialogue critique avec J. L. Austin, le fondateur de la théorie du discours performatif, mais aussi avec Sigmund Freud, Michel Foucault, Pierre Bourdieu, Jacques Derrida ou encore Catharine MacKinnon, elle s'efforce d'établir l'ambivalence du hate speech, de la violence verbale et des discours de haine homophobes, sexistes ou racistes : s'ils peuvent briser les personnes auxquelles ils sont adressés, ils peuvent aussi être retournés et ouvrir l'espace nécessaire d'une lutte politique et d'une subversion des identités. Elle esquisse ainsi une défense pragmatique du principe de la liberté d'expression, qui ne s'en tient pas aux arguments employés classiquement par les doctrines libérales, mais est surtout préoccupée par le souci de maximiser la puissance d'agir des dominés et des subalternes. Les lecteurs français trouveront dans ce livre des instruments inédits pour repenser à nouveaux frais les questions soulevées par les débats sur la pénalisation des discours de haine.
Première publication: 1997
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; états-unis

Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

No future: Queer theory and the death drive - Edelman, Lee (Duke University Press., 2004)
In this searing polemic, Lee Edelman outlines a radically uncompromising new ethics of queer theory. His main target is the all-pervasive figure of the child, which he reads as the linchpin of our universal politics of “reproductive futurism.” Edelman argues that the child, understood as innocence in need of protection, represents the possibility of the future against which the queer is positioned as the embodiment of a relentlessly narcissistic, antisocial, and future-negating drive. He boldly insists that the efficacy of queerness lies in its very willingness to embrace this refusal of the social and political order. In No Future, Edelman urges queers to abandon the stance of accommodation and accede to their status as figures for the force of a negativity that he links with irony, jouissance, and, ultimately, the death drive itself. Closely engaging with literary texts, Edelman makes a compelling case for imagining Scrooge without Tiny Tim and Silas Marner without little Eppie. Looking to Alfred Hitchcock’s films, he embraces two of the director’s most notorious creations: the sadistic Leonard of North by Northwest, who steps on the hand that holds the couple precariously above the abyss, and the terrifying title figures of The Birds, with their predilection for children. Edelman enlarges the reach of contemporary psychoanalytic theory as he brings it to bear not only on works of literature and film but also on such current political flashpoints as gay marriage and gay parenting. Throwing down the theoretical gauntlet, No Future reimagines queerness with a passion certain to spark an equally impassioned debate among its readers
Keywords: amériques; approches et analyses; cinéma; communication; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; premier cycle; psychanalyse; queer; régions géographiques; sciences humaines; thématiques; violences; états-unis; études culturelles

Queer theory, butch/femme identities and lesbian space - Eves, Alison (Sexualities, 2004)
Queer theory has been criticized for its textual focus and lack of attention to the structural and to everyday social practices. This article is part of a wider attempt to draw on the different strengths and insights of queer theory and qualitative social sciences. I identify areas of intersection between them which suggest potential ways of developing a queer sociology. The article considers the negotiation of gender and sexual identity categories at the level of individual butch and femme identity narratives. The concept of interpretative repertoires is used to theorize the ways in which lesbians are both positioned by and actively negotiate particular discourses. I am interested in the spatial aspects of the negotiation and contestation of identities and the article examines the ways in which particular interpretative repertoires produce butch and femme metaphorical and material spaces. The article draws on a concept of space as fluid, contested in meaning and created through social interactions. The achievement of lesbian visibility is examined as a strategic intervention in the establishment of subcultural space in which lesbian genders may be performed and read in specifically lesbian ways. Butch and femme aesthetics are examined as tactics in resisting heterosexual space and demanding lesbian presence.
Keywords: approches et analyses; discipline; genre; hétérosexisme; personnes lesbiennes; queer; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (University of Minnesota Press, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Publisher: Taylor & Francis
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Séparation, monoparentalité et recomposition familiale: bilan d'une réalité complexe et pistes d'action - Saint-Jacques, Marie-Christine (Presses de l'Université Laval, 2004)
Trente pour cent des jeunes québécois ne vivent pas, au quotidien, avec leurs deux parents d'origine. Le Québec compte 20 % de familles monoparentales et 10 % de familles recomposées. De 7 % à 33 % des gais et lesbiennes ont des enfants. Voilà autant de chiffres qui témoignent des transformations profondes que connaît la famille, phénomène généralisé en Amérique du Nord que l'on observe aussi dans plusieurs pays européens. La question de la séparation des parents n'est pas nouvelle. Après avoir porté un regard inquiet sur ses conséquences sur le devenir des enfants, on en vient pratiquement aujourd'hui à la banaliser. Pourtant, elle demeure une expérience unique pour les enfants et les parents, comportant son lot de stresseurs, de peines, de déceptions, de conflits, de rééquilibre et de réorientation vers de nouvelles avenues, comme la vie au sein d'une famille monoparentale et la recomposition familiale. S'appuyant sur un nombre colossal d'études, des chercheurs québécois livrent dans cet ouvrage un regard critique sur différents aspects de la vie familiale après la séparation des parents, tels l'adaptation des jeunes, la recomposition familiale, les conflits et la violence conjugale, l'incarcération d'un parent, la paternité, l'homoparentalité, le rôle des milieux de garde et de l'école et la médiation familiale de même qu'une mise en contexte historique. Séparation, monoparentalité et recomposition familiale est un ouvrage incontournable pour le lecteur qui souhaite être au fait des dernières connaissances dans le domaine des transitions familiales. Il vise tout autant les personnes qui interviennent auprès d'enfants, d'adolescents et de parents que les chercheurs et les étudiants du domaine.
Section: xxvi, 442 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; famille recomposée; familles homoparentales; identités LGBTQIA2+; maternité; parentalité; premier cycle; privilèges; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Queer theory, gender theory an instant primer - Wilchins, Riki Anne (Alyson Books, 2004)
Queer Theory, Gender Theory: An Instant Primer is a classic of LGBTQ+ literature and is taught in most gender studies programs throughout the United States. It was the first book to offer a one-stop, no-nonsense introduction to the core of postmodern theory, particularly its impact on queer and gender studies and is still powerfully relevant today. Nationally-known gender activist Riki Wilchins combines straightforward prose with concrete examples from LGBTQ+ and feminist politics, as well as her own life, to guide the reader through the foundational ideas of Derrida, Foucault, and Judith Butler that have forever altered our understanding of bodies, sex and desire. This is that rare postmodern theory book that combines accessibility, passion, personal experience and applied politics, noting at every turn why these ideas matter and how they can affect your daily life.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; fem1000; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; thématiques; théories féministes; états-unis